1873 Nev. Stat. 118 - (:unkn) unknown (My University, 1873)
Ch. 62, § 1.: Any person in this State, having, carrying, or procuring from another person, any dirk, dirk knife, sword, sword cane, pistol, gun, or other deadly weapon, who shall in the presence of two or more persons, draw or exhibit any of said deadly weapons, in a rude, angry, or threatening manner, not in necessary self-defense, or who shall in any manner unlawfully use the same in any fight or quarrel, the person or persons so offending shall be deemed guilty of a misdemeanor, and on conviction thereof shall be fined in any sum not exceeding five hundred dollars, or shall be imprisoned in the County Jail for a term not exceeding six months
Keywords: BRANDISHING; DUELING